Implikasi Dance Cuci Tangan Enam Langkah terhadap Kemampuan Cuci Tangan Siswa pada Masa New Normal - Swaidatul Masluhiya AF; Sirli Mardianna Trishinta; Anung Prasetyo Nugroho (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Six steps handwashing using soap and running water is one of the efforts to prevent disease. This study aims to determine the implications of the six-step handwashing dance on students' handwashing abilities during the new normal period at SDN 1 Landungsari, Dau District, Malang Regency. The design in this study was pre-experimental with a one-group pretest-posttest design that involved a sample of 77 students using a purposive sampling method. The instrument employed in this study was in the form of a 6-step handwashing questionnaire. The data was analyzed using a T-Test. The inclusion criteria in this study were elementary school students in grades IV, V, and VI, present at the time of the study, participated in the study and were willing to take the pretest and posttest. Frequent handwashing is one of the effective steps to prevent the transmission of COVID-19. Based on the study results, it was known that before the six-step handwashing dance (pre-test), respondents were not able to wash their hands properly and correctly. This was indicated by the wrong movements during the six-step handwashing practice. After being taught the six-step handwashing dance (post test), almost all of the respondents were able to wash their hands properly and correctly. The ability of respondents increased by 67.53%. Paired Sample T-Test results in a value of Sig. (2-tailed) 0.00 < 0.05 which can be concluded that there is an implication of the six-steps handwashing ability for students of SDN 01 Landungsari Malang Regency. This is because the material about the six steps of good and correct handwashing was delivered in an interesting method so that respondents could accept and remember the material easily.Keywords: Baby shark; COVID-19; six-steps handwashing; dance; ability.